The moderating effect of organisational culture on the relationship between workplace learning and employees performance in the United Arab Emirates - Hasan, Al Hammadi Faisal Ahmed Ali (Tanjong Malim, 2022)
The moderating effect of organisational culture on the relationship between workplace learning and employees performance in the United Arab Emirates by Hasan, Al Hammadi Faisal Ahmed Ali